The anticipation of working experiences among students from private institutes in Klang Valley: A qualitative perspective - Law, Kyra; Kue, Wei Xin (International Business Education Journal, 2020)
As university students are entering a competitive workforce, getting a desirable job has become more demanding. Many universities offer industrial training or internship placements in their degree programmes. Thus, this study provides a qualitative perspective of anticipation of working experiences among university students in Klang Valley. This study is carried out in the form of face-to-face semi-structured interviews with ten university students in Klang Valley. The contents are analyzed by its content and code in themes. The results show that the anticipations of working experiences among university students fall into a few categories which are; relevant education, purposes and importance of working experiences as well as the challenges faced in the workforce. This study closes the gap between workforce expectation and students’ impractical expectations as it gives university students a better insight about working experience especially during their studies so that they can pre-plan their future. Overall, this study can benefit future university students by improving their expected skills which will lead to higher employers’ satisfaction.